2016
DOI: 10.1016/j.neurobiolaging.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between shift work history and performance on the trail making test in middle-aged and elderly humans: the EpiHealth study

Abstract: Shift work has been proposed to promote cognitive disturbances in humans; however, conflicting evidence is also present. By using data from 7143 middle-aged and elderly humans (45-75 years) who participated in the Swedish EpiHealth cohort study, the present analysis sought to investigate whether self-reported shift work history would be associated with performance on the trail making test (TMT). The TMT has been proposed to be a useful neuropsychological tool to evaluate humans' executive cognitive function, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
47
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 40 publications
5
47
2
1
Order By: Relevance
“…The lack of evidence of an association of shift work with cognitive level and change agrees with what has been reported in the Nurse's Health Study (10), but not with that in other studies (12,28). Marquie et al (12) observed shift work to be prospectively associated with poorer memory and speed performance and was the first study to report that cognitive performance did not differ between day workers and former shift workers who had left shift work for ≥5 years.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The lack of evidence of an association of shift work with cognitive level and change agrees with what has been reported in the Nurse's Health Study (10), but not with that in other studies (12,28). Marquie et al (12) observed shift work to be prospectively associated with poorer memory and speed performance and was the first study to report that cognitive performance did not differ between day workers and former shift workers who had left shift work for ≥5 years.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, our study controlled for educational differences and employed an intra-individual approach to assess the association between shift work and cognition, which altogether may have led to diverging findings. Titova et al (28) similarly reported that shift work was associated with poorer executive cognitive function, though the cross-sectional study design and not accounting for neurodegenerative disease suggest findings should be interpreted cautiously. The present study's findings together with those of the Nurse's Health Study (10) lead to the conclusion that there is no association of shift work with cognitive ability and change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, considering the reversible changes in the inflammatory markers after quitting shift work, there might be some differences in the inflammatory markers between former shift workers who have performed shift work in recent years and former shift workers who have not performed shift work in recent years, even if their duration of shift work was the same. In a study by Titova et al, former shift work was categorized according to a criterion of 5 years: past shift workers were those who did not perform shift work during the past 5 years but had worked night shifts more than 5 years ago, and recent former shift workers were defined as those who performed shift work during the past 5 years but not at the time of data collection; greater impairment of cognitive function was observed in current and recent former shift workers than in non-shift workers, while there was no significant difference between non-shift workers and past shift workers [ 48 ]. Because most studies on the association between shift work and CVD did not present clear-cut criteria for former shift worker, future studies need to take this into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is some preliminary evidence that shift work may adversely influence cognitive functions. Titova et al (16) observed that current and recent former shift workers performed worse on a trailmaking test, which measures executive cognitive function, compared with non-shift workers.…”
mentioning
confidence: 99%